Prolégomènes à toute appréciation critique de CANDIDE - Chabot-Plante, Francine; Hébert, Maurice; Waslander, H. (L'Actualité économique, 1975)
AbstractThis text describes the CANDIDE model from three critical points of view. First, it presents the structure of the model with the aid of a table of "supersectors" and a flow chart. The discussion of the linkages between these supersectors brings out the general equilibrium character of the model.The center section of the paper deals with the theoretical foundations of the behavioural equations. A statement of the equation specification in each sector of the model is followed by a brief evaluation. The authors confess to an eclectic attitude and stress the practical difficulties of making stylized theories bring order in variegated facts. Exogenous influences on the model are discussed as well.The same eclectic approach is evident in the third part of the text which treats of estimation and validation. A variety of tests and checks—some novel ones included—are applied in the process of developing the model. The authors conclude with the observation that recent tumultuous developments in the economy raise fundamental questions about the validity and usefulness of models like CANDIDE.